2017
DOI: 10.12788/jhm.2857
|View full text |Cite
|
Sign up to set email alerts
|

Do Combined Pharmacist and Prescriber Efforts on Medication Reconciliation Reduce Postdischarge Patient Emergency Department Visits and Hospital Readmissions?

Abstract: A long-term, observational evaluation of interprofessional Med Rec did not detect a difference in 30- day postdischarge patient hospital visits between patients who received enhanced versus partial Med Rec patient care bundles. In future prospective studies, researchers could focus on evaluating high-risk populations and specific elements of Med Rec services on avoidable, medication-related hospital admissions and postdischarge adverse drug events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Compared with the control, length of stay decreased by a mean of 0.73 days with the pharmacist‐hospitalist collaboration model ( P = .002). Findings from several studies describing interprofessional medication reconciliation teams have demonstrated mixed results with beneficial outcomes such as decreased medication errors, reduced hospitalist time on inpatient admissions, and significant cost avoidance, but no differences in 30‐day readmission rates 5‐8 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with the control, length of stay decreased by a mean of 0.73 days with the pharmacist‐hospitalist collaboration model ( P = .002). Findings from several studies describing interprofessional medication reconciliation teams have demonstrated mixed results with beneficial outcomes such as decreased medication errors, reduced hospitalist time on inpatient admissions, and significant cost avoidance, but no differences in 30‐day readmission rates 5‐8 …”
Section: Introductionmentioning
confidence: 99%
“…Findings from several studies describing interprofessional medication reconciliation teams have demonstrated mixed results with beneficial outcomes such as decreased medication errors, reduced hospitalist time on inpatient admissions, and significant cost avoidance, but no differences in 30-day readmission rates. [5][6][7][8] Since institutions have been employing hospitalists for years, it is…”
mentioning
confidence: 99%
See 3 more Smart Citations